2005
DOI: 10.1016/j.jcis.2005.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial forces and Marangoni flow on a nematic drop retracting in an isotropic fluid

Abstract: Nematic-isotropic interfaces exhibit novel dynamics due to anchoring of the liquid crystal molecules on the interface. The objective of this study is to demonstrate the consequences of such dynamics in the flow field created by an elongated nematic drop retracting in an isotropic matrix. This is accomplished by two-dimensional flow simulations using a diffuse-interface model. By exploring the coupling among bulk liquid crystal orientation, surface anchoring and the flow field, we show that the anchoring energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…Yue et al [7,11] have shown how the model can be extended to non-Newtonian fluids, and developed the AMPHI algorithm in two dimensional geometries based on finite elements with adaptive meshing [20]. The main ideas of the 3D algorithm are close to those in 2D.…”
Section: A Diffuse Interface Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Yue et al [7,11] have shown how the model can be extended to non-Newtonian fluids, and developed the AMPHI algorithm in two dimensional geometries based on finite elements with adaptive meshing [20]. The main ideas of the 3D algorithm are close to those in 2D.…”
Section: A Diffuse Interface Modelmentioning
confidence: 99%
“…In this section, we will briefly summarize these ideas and give the governing equations, using the mixture of a Newtonian and an Oldroyd-B fluid as an example. The method accommodates other types of complex fluids such as nematic liquid crystals [11,23,24,29,30], but we will confine this paper to Newtonian-Newtonian and Newtonian-Oldroyd-B mixtures.…”
Section: A Diffuse Interface Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important consequence of interfacial relaxation is the change in apparent interfacial tension [41,43]. To simulate an experiment with two immiscible fluids, one chooses appropriate values for the mixing energy λ and capillary width so as to match λ/ to the experimental interfacial tension σ according to a formula based on some equilibrium φ profile [34,41].…”
Section: Interfacial Relaxation Secondary To the Ambiguity In Interfa-mentioning
confidence: 99%
“…Taking advantage of the energy-based formulation, they are able to resolve the dual difficulties for complex fluid mixtures-moving interfaces and complex rheology-in a unified framework. So far, Yue and coworkers have applied the method to a number of problems on drop dynamics of viscoelastic and liquid crystalline fluids [42][43][44][45][46]. In the following, we first give a brief but self-contained derivation of the theoretical model, and describe a numerical algorithm using spectral methods.…”
mentioning
confidence: 99%